Dynamic characteristics of dough during the fermentation process of Chinese steamed bread. (15th May 2020) - Chang, Xianhui; Huang, Xingyi; Tian, Xiaoyu; Wang, Chengquan; Aheto, Joshua H.; Ernest, Bonah; Yi, Ren
Highlights: Investigated the changes in various indicators of dough during fermentation. There was no significant change in starch-paste properties, T21, and T22 of dough. VOCs and FAAs of the dough change significantly, but no rule was established. The change of headspace was most suitable for monitoring the fermentation of dough. 3 fermentation states of dough could be accurately identified by using E-nose. Abstract: The fermentation process is crucial to the production of Chinese steamed bread (CSB). In order to select suitable indicators as the basis for further research of establishing intelligent monitoring method for dough fermentation state, this study investigated the dynamic characteristics of dough during fermentation. Indicators included water mobility and distribution, starch-pasting properties, content of free amino acid (FAA), volatile organic compounds (VOCs) and electronic nose (E-nose) response value. Starch-pasting properties of dough and relaxation time (T21, T22 ) did not change significantly during the fermentation process (p < 0.05). The VOCs and FAAs of the dough had significant differences (p < 0.05) in different fermentation times, but no rule was established. The E-nose response value to headspace was most suitable to monitor the fermentation of dough. Principal component analysis (PCA) was performed on E-nose data from 75 samples and the results indicated that samples of different fermentation states were accurately classified.